An Investigation of Assessed Writing Requirements at Undergraduate Level in the Humanities - Turner, Elizabeth (Auckland University of Technology, 2005)
English for Academic Purposes (EAP) courses play an increasingly important role in supporting non English speaking background students in their academic studies. Such courses have traditionally prioritised writing as the most significant literacy requirement (Johns, 1981). This prioritisation of writing reflects the perception that expertise in writing is an indication that students have acquired the cognitive skills demanded for university work (Weigle, 2002). It also reflects the fact that the majority of assessment tasks, which tend to drive student learning (Schwartz & Webb, 2002), require some form of writing. For EAP courses to be effective, curriculum design needs to be informed by knowledge of current academic discourse demands and writing requirements in relevant discipline areas. Analysis of previous studies indicates that written assessment tasks vary between discipline areas. Findings also suggest that the most frequent assessment types vary over time as theoretical approaches to assessment change. This suggests the need to investigate the discipline-specific demands faced by different student cohorts enrolled on EAP courses. Some studies have identified the need for students to develop the skills involved in interpreting task instructions, as well as addressing the relevant topic and meeting the specific assessment requirements (Gravatt et al., 1997 and Carson, 2001). A key impetus for this study relates to this finding and was the fact that students enrolled on EAP courses were having difficulties interpreting instructions and marking criteria provided for some assessments in discipline-specific papers. The aims of this study were three-fold. The first was to investigate and analyse the type and form of written assessment tasks and related requirements, in three undergraduate courses. The second was to investigate lecturers' perceptions and intentions in producing these tasks. Thirdly, the study aimed to investigate and describe students' understandings and experiences of the same tasks. The study therefore involved a triangulated methodology in terms of data collection. The three methods employed were analysis of assessment documents, semi-structured interviews with the lecturers concerned, and questionnaire surveys of students enrolled on the three papers. The results of the study reinforce the findings of earlier studies in that there are considerable differences between discipline areas in assessment types and in the levels of associated cognitive demands. Although the study identifies what appears to be a new assessment type at undergraduate level - the 'literature review' assignment - lecturers' expectations for this assessment appear to vary between discipline areas. The differences identified appear to be influenced by lecturers' perceptions of the role of assessment, which in this case seem to be limited to the concept of assessment as the certification of learning, and as being predominantly summative in function. Furthermore the study shows that a significant proportion of student respondents found the majority of assessment instructions difficult to understand, and that only one of the papers provided assessment criteria. The findings suggest that the absence of explicit marking criteria appears to disadvantage non-English speaking background students in particular. The conclusions of the thesis focus primarily on the dual, 'critical pragmatic', role of EAP practitioners in seeking to inform curriculum design and also to influence assessment practice; the implications of the study for the university's assessment and academic literacy policies and their implementation; the implications of the findings for EAP curriculum design, and suggestions for future research.
Keywords: Academic writing; Education